Navigating Energy Market Cycles: Insights from a Comprehensive Analysis - Alqaralleh, Huthaifa; Almajali, Awon; Canepa, Alessandra (International Journal of Energy Economics and Policy, 2024)
In this article, we investigate the dynamics the intricacies of fluctuations during periods of economic expansion and contraction, and examining the connections between the length of energy cycles and the influential factors could affect them. Utilizing the extended BBQ algorithm, we firstly identify turning points and, then apply the Cox hazard Model to analyze factors that affect the cycle phases, including geopolitical conflict and economic situations over the period from January 1990 to July 2022. The results reveal the presence of asymmetry in growth phases, highlighting the need for policymakers to understand the factors driving these phases. Market expansion is driven by positive interest rate and US dollar shocks, while stability relies on competent management. During economic contractions, energy costs are influenced by economic growth. Geopolitical risks and economic uncertainty require effective risk mitigation, and policy changes significantly impact the energy market during expansion phases. The study also suggests that Conferences of Parties (COP) meetings have a nuanced influence on the energy market, warranting further research.